Soil fertility based on mineralogical properties to support sustainable agriculture management - Hidayat, Wahyu; Suryaningtyas, Dyah Tjahyandari; Mulyanto, Budi (Universitas Sebelas Maret, 2024)
Detailed information on soil mineral composition has been crucial in providing the basis for designing sustainable agricultural practices, as this information offers long-term insights into natural soil fertility. This research aimed to further investigate the characteristics of soil mineral composition as a basis for managing soil fertility. Three soil profiles representing three different parent materials have been examined in the field, and soil samples have been collected for laboratory analysis. Profile 1 originates from the Raung Volcano Rock Formation (Qhvr). Profile 2 originates from the Sukamade Formation (Toms). Profile 3 originates from Puger Formation (Tmp). The presence of Mount Raung volcanic influence results in distinct soil characteristics in Profiles 2 and 3 compared to typical sedimentary and karst rock soils. The sand fraction minerals in all three profiles are predominantly composed of opaque minerals, followed by rock fragments, ferromagnesian mineral series (olivine, augite, hypersthene, and hornblende), plagioclase minerals (anorthite, biotite, and labradorite), iron concretions, epidote, and tourmaline. The clay fraction minerals in all three profiles consist of illite, kaolinite, and quartz. The minerals illite and ferromagnesian groups in all three profiles play a significant role in increasing the availability of potassium, calcium, and magnesium nutrients, thereby reducing the need for fertilizers for these elements. The soils in all three profiles naturally possess good fertility; however, designing a sustainable agricultural system requires consideration of the morphology, landform, and climate of all three profiles.